2018
DOI: 10.1016/j.neuroscience.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity Mechanisms of Memory Consolidation and Reconsolidation in the Perirhinal Cortex

Abstract: In this review we explore the role of the perirhinal cortex (Prh) in memory, focusing on the cellular and molecular mechanisms that have been described to happen in this structure. The Prh is part of the medial temporal lobe, but the evidences show that it has a different function than that of the hippocampus. In particular, the Prh is known to be important for object recognition memory, although it could have a role in other types of memory. However, despite the fact that object recognition tasks are widely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 203 publications
0
20
0
Order By: Relevance
“…It is supported by networks of interdependent brain regions involving the medial temporal lobe and prefrontal cortex 26,48,78 which are selectively activated depending on the type and features being recognized. Recognition memory of single items needs the integrity of the PRh while recognition of an object and its spatial location requires also the HP and medial prefrontal cortex functions 27,[79][80][81][82] . We found that the aRSC functional integrity is required during recognition LTM consolidation in all variants of the task we used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is supported by networks of interdependent brain regions involving the medial temporal lobe and prefrontal cortex 26,48,78 which are selectively activated depending on the type and features being recognized. Recognition memory of single items needs the integrity of the PRh while recognition of an object and its spatial location requires also the HP and medial prefrontal cortex functions 27,[79][80][81][82] . We found that the aRSC functional integrity is required during recognition LTM consolidation in all variants of the task we used.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of these components creates a unique memory. In addition, the RSC is connected with the perirhinal cortex (PRh) 16 , the prime structure involved in object recognition memory [25][26][27] . Despite the potential role of the RSC in recognition memory, its precise involvement in the "what" memory component encoding remains unknown.…”
mentioning
confidence: 99%
“…The activation of the PRC was also related to subsequent item memory of the "same" and "similar" (vs "different") objects. The PRC could thus be regarded as a region implicated in pattern separation (Burke et al, 2010;Yassa and Stark, 2011;Leal and Yassa, 2018;Miranda and Bekinschtein, 2018) of two similar objects when they are simultaneously presented. Pattern separation refers to the ability to discriminate among similar experiences, thus they are stored in a distinct, nonoverlapping representations .…”
Section: Prc and Phc In Discriminative Learning And Predicting Subseqmentioning
confidence: 99%
“…SI and SII are considered to sit at similar levels of cortical hierarchy and both project to PV and PR (Krubitzer et al, 1986). PR cortex projects to entorhinal cortex and hence somatosensory information can reach the hippocampus by this route (Miranda and Bekinschtein, 2017).…”
Section: Corticocortical Projections: Dorsal and Ventral Streamsmentioning
confidence: 99%